Motor Functional Reorganization Is Triggered by Tumor Infiltration Into the Primary Motor Area and Repeated Surgery - Nakajima, Riho; Kinoshita, Masashi; Nakada, Mitsutoshi (Frontiers in Human Neuroscience, 2020)
In patients with gliomas, motor deficits are not always observed, even though tumor cells infiltrate into the motor area. Currently, it is recognized that this phenomenon can occur through the neuroplasticity potential. Aim of this study is to investigate the characteristics of motor functional reorganization in gliomas. Out of 100 consecutive patients who underwent awake surgery, 29 patients were aimed to assess motor function, and were retrospectively explored whether positive motor responses were elicited. Totally 73 positive mapping sites from 27 cases were identified and their spatial anatomical locations and activated region by functional MRI were analyzed. Additionally, the factors promoting neuroplasticity were analyzed through multiple logistic regression analysis. As a result, totally 60 points (21 cases) were found in place, while 13 points (17.8%) were found to be shifted from anatomical localization. Reorganizations were classified into three categories: Type 1 (move to ipsilateral different gyrus) was detected at 9 points (4 cases), and they moved into the postcentral gyrus. Type 2 (move within the ipsilateral precentral gyrus) was detected at 4 points (2 cases). Unknown type (2 cases) was categorized whose motor functional cortex was moved to other regions, although we could not find compensated motor area. Two factors for the onset of reorganization were identified: tumor cells infiltrate into the primary motor area, and repeated surgery (p<.0001 and p=0.0070, respectively). Our study demonstrated that compensation can occur mainly in two ways, and it promoted by repeated surgery and infiltration of tumor into the primary motor area.